A sense of shame among the virtues. Issue 2 (2nd April 2016) - Nichols, Ryan
Abstract: The purpose of this article is to pose and preliminarily answer the question, 'Can the sense of shame be a virtue?' It offers a brief, empirically informed, affirmative answer to this question. After developing the context of this question, the article describes the emotion of shame and the shame system by situating them in their evolutionary and cultural contexts. This positions us to address Aristotelian reasons for a negative answer to our question having to do with whether shame is merely an emotion (no) and whether the sense of shame functions as a disposition to decide (yes). We summarize the evolutionary purpose of shame as a social-rank based emotion and identify benefits accruing to a population in which the sense of shame is working well.